Advances in Biomedical Informatics - Holmes, Dawn E.; Jain, Lakhmi C. (Intelligent Systems Reference Library,, 2018)
This book presents authoritative recent research on Biomedical Informatics, bringing together contributions from some of the most respected researchers in this field. Biomedical Informatics represents a growing area of interest and innovation in the management of health-related data, and is essential to the development of focused computational models. Outlining the direction of current research, the book will be of considerable interest to theoreticians and application scientists alike. Further, as all chapters are self-contained, it also provides a valuable sourcebook for graduate students.